Keterkaitan Kualitas Air dengan Keanekaragaman Zooplankton di Sungai Barito Kecamatan Marabahan Kabupaten Barito Kuala - Sofarini, Dini; Aminah, Siti; Nur Hidayah, Rina; Septa Hanifa, Marissa (Rekayasa, 2021)
The fish diversity in Barito River is determined by diversity of zooplankton, in relation to the grazing food chain’s concept. One of the problems that occur is the quality of several key parameters in waters are no longer suitable for zooplankton and fish life. The purpose of this research were: (a) analyze the key parameters of water quality at the sampling location (b) determine the relationship between key water quality parameters and zooplankton diversity at the Barito River sampling location. The method used was a purposive sampling survey method and the shanon-wiener method. The results showed that the key parameters that met the PP No. 22/2021 Water Quality Standard for Class 2 River Water Quality.